2017
DOI: 10.1111/ppa.12738
|View full text |Cite
|
Sign up to set email alerts
|

Transmission attributes and resistance to rose rosette virus

Abstract: Rosette caused by rose rosette virus (RRV) is a devastating disease of rose in the United States. The virus was discovered in 2011 and Koch's postulates completed in 2015. Because of these recent discoveries, assumptions about the disease including movement, transmission and resistance are based on visual observations of material that may or may not have been infected by the virus. This study addresses several aspects of virus and disease dynamics. Twenty rose genotypes were screened for mite and/or virus resi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 21 publications
(39 reference statements)
4
37
0
Order By: Relevance
“…For a small number of samples, the protocol of Poudel et al [25] was used. All samples were tested by RT-PCR [26] to confirm the presence of the virus.…”
Section: Plant Materials and Nucleic Acid Extractionmentioning
confidence: 99%
“…For a small number of samples, the protocol of Poudel et al [25] was used. All samples were tested by RT-PCR [26] to confirm the presence of the virus.…”
Section: Plant Materials and Nucleic Acid Extractionmentioning
confidence: 99%
“…Nevertheless, early detection is crucial, and identification and eradication of infected plants are necessary for effective control of RRD (Hong et al ., 2012). Pruning out parts of plants with symptoms does not eliminate the virus and should be avoided to minimize the persistence of the virus after overwintering in the root system (Di Bello et al ., 2017). Ideally, all multiflora roses in a 100 m radius should be removed, because they serve as a source of inoculum for RRV (Department for Environment, Food and Rural Affairs, 2016).…”
Section: Rose Rosette Virusmentioning
confidence: 99%
“…Other symptoms that may be expressed are darkening of canes, short internodal distances, blind shoots, rough leaf texture, and an increased susceptibility to infection, especially by fungal diseases (Hong et al ., 2012). Infected plants die within 3–5 years of becoming infected (Di Bello et al ., 2017).…”
Section: Rose Rosette Virusmentioning
confidence: 99%
“…Non-viruliferous mites will acquire RRV by feeding on infected plants for a certain time period (acquisition access period) (EPPO, 2018). Di Bello et al (2018) demonstrated that the minimum acquisition access period for RRV is 5 days. It has been shown that other emaraviruses, namely maize red stripe virus and wheat streak mosaic virus do not have transovarial transmission by their vector Aceria tosichella (Mielke-Ehret and Mühlbach, 2012).…”
Section: Life Cycle Of Phyllocoptes Fructiphilusmentioning
confidence: 99%
“…Dobhal et al (2016) tested the assay on 30 field-collected infected samples, which were all successfully rated as positive, suggesting a 100% diagnostic sensitivity within the limits of this study. Di Bello et al (2018) worked on an amended protocol based on that first described by Laney et al (2011); however, they did not record diagnostic sensitivity or detection success rate in any way. Lastly, Laney et al (2011) reported that all 84 symptomatic plant samples collected for testing, tested positive while the 30 symptomless plants tested negative.…”
Section: Reverse-transcription Pcr (Rt-pcr)mentioning
confidence: 99%